FEATURES FOR TEACHING SCHOOL MATHEMATICS THROUGH STEM EDUCATION - Slyamova M.S; Kokazhaeva А.B (Progress in Science, 2024)
This article presents a review of research papers in which a school examined a mathematics course on the necessity and effectiveness of teaching through STEM education. The main purpose of the study- to examine the benefits and necessity of using STEM education in teaching mathematics and the effectiveness of determining how it affects mathematics teaching.